Analysis of Social Conflict in Denny Caknan's Satru Song (Study of the Sociology of Literature) - Nurhikmah, Selviana (Universitas PGRI Semarang, 2024)
Conflict is a disagreement or difference between two people or groups. Conflict is a part of social life, social conflict is also motivated by differences of opinion brought by individuals in an interaction. Everyone has different characteristics, characteristics and ways of thinking. The existence of differences can make it difficult for people to accommodate themselves, so it can easily trigger some things that lead to conflict. The interests of an individual or group also sometimes clash. Thus, this will lead to conflict between them as well. As in this analysis, this study examines the song popularized by Denny Caknan, namely